If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (p + -5) * x(3p + 2) = 0 Reorder the terms: (-5 + p) * x(3p + 2) = 0 Reorder the terms: (-5 + p) * x(2 + 3p) = 0 Reorder the terms for easier multiplication: x(-5 + p)(2 + 3p) = 0 Multiply (-5 + p) * (2 + 3p) x(-5(2 + 3p) + p(2 + 3p)) = 0 x((2 * -5 + 3p * -5) + p(2 + 3p)) = 0 x((-10 + -15p) + p(2 + 3p)) = 0 x(-10 + -15p + (2 * p + 3p * p)) = 0 x(-10 + -15p + (2p + 3p2)) = 0 Combine like terms: -15p + 2p = -13p x(-10 + -13p + 3p2) = 0 (-10 * x + -13p * x + 3p2 * x) = 0 Reorder the terms: (-13px + 3p2x + -10x) = 0 (-13px + 3p2x + -10x) = 0 Solving -13px + 3p2x + -10x = 0 Solving for variable 'p'. Factor out the Greatest Common Factor (GCF), 'x'. x(-13p + 3p2 + -10) = 0 Factor a trinomial. x((p + -5)(3p + 2)) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing p to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x = 0 + -1x Remove the zero: 0 = -1x Simplifying 0 = -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(p + -5)' equal to zero and attempt to solve: Simplifying p + -5 = 0 Reorder the terms: -5 + p = 0 Solving -5 + p = 0 Move all terms containing p to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + p = 0 + 5 Combine like terms: -5 + 5 = 0 0 + p = 0 + 5 p = 0 + 5 Combine like terms: 0 + 5 = 5 p = 5 Simplifying p = 5Subproblem 3
Set the factor '(3p + 2)' equal to zero and attempt to solve: Simplifying 3p + 2 = 0 Reorder the terms: 2 + 3p = 0 Solving 2 + 3p = 0 Move all terms containing p to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3p = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3p = 0 + -2 3p = 0 + -2 Combine like terms: 0 + -2 = -2 3p = -2 Divide each side by '3'. p = -0.6666666667 Simplifying p = -0.6666666667Solution
p = {5, -0.6666666667}
| 2d-7=-13 | | 5X^2-40X+90=0 | | 5(2+c)=4(c-4) | | 4x+38=14x-82 | | y-45=6y | | -7(x+4)-12=22+1 | | 4(4x-6)=17x | | 23423x^2-90=90-89x | | 2+10=24 | | 7w-12w=10 | | 12-6x=3x+7 | | 2m-7=-5m-12 | | 3(2d+5)=4d | | 9-5x=35 | | a^2-6b+8=0 | | 34-1=25+46 | | 4a+a+3a= | | 4a+8b=28 | | 4a+5b=22 | | 7p+5q=65 | | 3p+5q=45 | | q^2+(4*q^2)*(q^2)=1000 | | 3x-9x+6= | | 11x-42= | | 40x+.15=41.55 | | 1.035x+.15=41.55 | | .965x+.15=41.55 | | Y^2=y | | 2*4x=16 | | .965x+.15=40 | | 1.035x+.15=40 | | x-((1.035)x+.15)=40 |